Training counteracts DEX-induced microvascular rarefaction by improving the balance between apoptotic and angiogenic proteins - Jesus, Isley [UNESP]; Herrera, Naiara A. [UNESP]; Andreo, Jesus C.; Santos, Carlos F.; Amaral, Sandra L. [UNESP] (Elsevier, 2020)
This work investigated the mechanisms induced by exercise training that may contribute to attenuate dexamethasone (DEX)-induced microvascular rarefaction and hypertension. Wistar rats underwent training protocol or were kept sedentary for 8 weeks. Dexamethasone was administered during the following 14-days and hemodynamic parameters were recorded at the end. Capillary density (CD) and capillary-to-fiber ratio (C:F ratio) were obtained in soleus muscle (SOL). Also, vascular endothelial growth factor (VEGF), vascular endothelial growth factor receptor-2 (VEGFR-2), endothelial nitric oxide synthase (eNOS), B-cell lymphoma 2 (Bcl-2), Bcl-2-like protein 4 (Bax), p-BAX and caspase-3 cleaved protein levels were analyzed. DEX treatment significantly increased blood pressure (+14%), which was associated with reduced C:F ratio (−41.0%) and CD (−43.1%). Reduction of vessel density was associated with decreased VEGF (−15.6%), VEGFR-2 (−14.6%), Bcl-2 (−18.4%), Bcl-2/Bax ratio (−29.0%) and p-Bax/Bax (−25.4%), and also with increased caspase-3 cleaved protein level (25%). Training, on the other hand, prevented microvessels loss by mitigating all proteins changes induced by DEX. In addition, angiogenic and apoptotic proteins were significantly correlated with CD, which, in turn, was associated with blood pressure. Therefore, we may point out that exercise training is a good strategy to attenuate DEX-induced microvascular rarefaction in soleus muscle and this response involves a better balance between apoptotic and angiogenic proteins, which may contribute for the attenuation of hypertension.
Keywords: Angiogenesis; Apoptosis; Blood pressure; Exercise training; Skeletal muscle; Steroid hormone